Enhanced mechanical and tribological properties in polyphenylene sulfide/polytetrafluoroethylene composites reinforced by short carbon fiber. (15th April 2016) - Luo, Wei; Liu, Qi; Li, Yi; Zhou, Shengtai; Zou, Huawei; Liang, Mei
Abstract: Self-lubricating composites based on Polyphenylene sulfide/Polytetrafluoroethylene (PPS/PTFE) reinforced with short carbon fibers (CF) were prepared by melt-blending. The effect of CF loadings on morphology, mechanical and dry-sliding behavior of the composite were carefully investigated in expectation of providing valuable information for the application of polymer-based composites. Results indicated that the incorporation of CF apparently improved the tensile strength, flexural modulus and hardness of PPS/PTFE blends. Meanwhile, the specific wear rate and average friction coefficient of PPS/PTFE reinforced by 15 vol% CF reached to 5.2 × 10 −6 mm 3 /Nm and 0.085, which are 88% and 47% lower than that of mono-PPS/PTFE blend at the same sliding condition. Scanning electron microscopy (SEM) observations of the worn surfaces revealed that the main wear mechanism of the PPS/PTFE composites transformed from adhesive wear to abrasive wear by the introduction of CF. X-ray photoelectron spectroscopy (XPS) analysis of worn surface and the macroscopic observations of steel ring counterpart indicated the existence of uniform, smooth and PTFE-rich transfer film for PPS/PTFE/CF trinary blends, which is responsible for the enhanced tribological properties.